SUPPLIER EVALUATION (Perner's Contacts, 2011)
This article deals with supplier evaluation by using scoring model. Supplier evaluation using scoring model is a quantitative evaluation of supplier according to predetermined criteria. The advantage of scoring is the transfer value of quantitative and qualitative criteria for the additive value, even taking into account the importance of different criteria, i.e. weight score.
Keywords: supplier; criterion; Saaty’s method